Answer:
2u + v - 4w = <40 , -4>
6u - 8v = <-78 , 58>
4v - 7w = <101 , -36>
11u + 3w = <-88 , 89>
Step-by-step explanation:
* Lets find the value of each operation to find its resultant vector
# 2u + v - 4w
∵ u = <-5 , 7>
∴ 2u = <-10 , 14>
∵ v = <6 , -2>
∵ w = <-11 , 4>
∴ 4w = <-44 , 16>
∴ 2u + v - 4w = <-10 + 6 - -44 , 14 + -2 - 16>
∴ 2u + v - 4w = <40 , -4>
# 6u - 8v
∵ u = <-5 , 7>
∴ 6u = <-30 , 42>
∵ v = <6 , -2>
∵8v = <48 , -16>
∴ 6u - 8v = <-30 - 48 , 42 - -16>
∴ 6u - 8v = <-78 , 58>
# 4v - 7w
∵ v = <6 , -2>
∴ 4v = <24 , -8>
∵ w = <-11 , 4>
∴ 7w = <-77 , 28>
∴ 4v - 7w = <24 - -77 , -8 - 28>
∴ 4v - 7w = <101 , -36>
# 11u + 3w
∵ u = <-5 , 7>
∴ 11u = <-55 , 77>
∵ w = <-11 , 4>
∴ 3w = <-33 , 12>
∴ 11u + 3w = <-55 + -33 , 77 + 12>
∴ 11u + 3w = <-88 , 89>
1289 -
943
First last number should be subtracted.
9 - 3 = 6
The second last
8 - 4 = 4
Then first number
2-9 = ?
Since it can't be divided, we have to borrow 10 from the previous number.
12-9 = 3
So the answer is,
346
Answer:
(2, -6)
Step-by-step explanation:
Because each equation is equal to y, you can plug the y equal to each other. Because one y is equal to -2x-2 and the other is 7x-20, you can set them equal to each other. So you should have
-2x - 2 = 7x - 20
The next step is to solve for x, which mean that x is 2, then plug 2 into one of the original equations ( it doesn't matter which one) and solve for y, and when you do that, you will get -6
Answer:
P=32cm
Step-by-step explanation:
Answer: only Kayla
Step-by-step explanation: